'Donut' basilar aneurysm with brainstem compression: Treatment using a flow diverting stent. Issue 3 (June 2016) - Maingard, Julian; Brooks, Mark
Partially thrombosed aneurysms with circular flow dynamics around central thrombus pose a therapeutic dilema. We demonstrate the successful treatment of a patient with a large basilar donut aneurysm with a flow diverting stent without the use of embolisation coils in order to obviate the risk of further brainstem compression.